2020
DOI: 10.1039/d0cc05781a
|View full text |Cite
|
Sign up to set email alerts
|

A carbene stabilized precursor for the spatial atomic layer deposition of copper thin films

Abstract: This is the first report on a plasma enhanced spatial atomic layer deposition (APP-ALD) process at atmospheric pressure to grow conducting metallic Cu thin films from a carbene stabilized precursor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…[51,52] The starting materials [Cu(NHC)(hmds)] and [Ag(NHC)(hmds)] which are used in all following reactions for the formation of the final complexes was synthesized and characterized using a procedure reported earlier by our group (Boysen et al). [31,32] [Cu(NHC)(acac)]: The starting material [Cu(NHC)(hmds)] (4.2 g, 10.3 mmol) is dissolved in 100 ml of hexane and acetylacetone (1.0 g, 10.3 mmol) is slowly added to the solution at RT and stirred. The resulting microcrystalline yellow precipitate is allowed to settle at the bottom of the flask after which the solvent is decanted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[51,52] The starting materials [Cu(NHC)(hmds)] and [Ag(NHC)(hmds)] which are used in all following reactions for the formation of the final complexes was synthesized and characterized using a procedure reported earlier by our group (Boysen et al). [31,32] [Cu(NHC)(acac)]: The starting material [Cu(NHC)(hmds)] (4.2 g, 10.3 mmol) is dissolved in 100 ml of hexane and acetylacetone (1.0 g, 10.3 mmol) is slowly added to the solution at RT and stirred. The resulting microcrystalline yellow precipitate is allowed to settle at the bottom of the flask after which the solvent is decanted.…”
Section: Methodsmentioning
confidence: 99%
“…At least for [Cu( tBu NHC)(acac)], a signal for the carbenic carbon atom could be located in the 13 C NMR spectrum at 203.16 ppm which is slightly shifted downfield compared to the already reported [Cu( tBu NHC)(hmds)] complex from our earlier studies (201.6 ppm) and indicates a smaller degree of π-back bonding from the metal to the carbene. [32] Nevertheless, a more detailed insight into the bonding situation for all complexes in the solid state and a validation of the results seen in NMR studies could be gained by SC-XRD measurements which are discussed in the next section.…”
Section: Nmr Spectroscopymentioning
confidence: 96%
See 1 more Smart Citation
“…[51] The starting materials [Cu(NHC)(hmds)] and [Ag(NHC)(hmds)] which are used in all following reactions for the formation of the final complexes was synthesized and characterized using a procedure reported earlier by our group (Boysen et al). [31,32] [Cu(NHC)(acac)]: The starting material [Cu(NHC)(hmds)] (4.2 g, 10.3 mmol) is dissolved in 100 ml of hexane and acetylacetone (1.0 g, 10.3 mmol) is slowly added to the solution at RT and stirred. The resulting microcrystalline yellow precipitate is allowed to settle at the bottom of the flask after which the solvent is decanted.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14] Recently, investigations into the structural parameters of metal-containing molecular precursors have been carried out in order to probe relationships between a precursor's molecular geometry (dictated by the bonding modes of the ligands bound to the metal) and their suitability for deposition. 15 For example, recent studies have shown that molecular complexes to be employed as precursors which crystallize with a distorted geometry are able to be deposited at lower temperatures due to their inherent molecular strain, 16,17 which can be quantified using the degree of distortion denoted as a ' value'. 18,19 Methods employed by synthetic chemists to control such parameters include varying the chemical nature of the complex by choosing specific ligands to perform certain functions.…”
Section: Introductionmentioning
confidence: 99%